Perancangan Assessment Value pada PT. XYZ dengan Menggunakan Metode Rasch - Christofer Kenny Yandra; I Nyoman Sutapa (Jurnal Titra, 2022)
This research was conducted to design a value assessment at PT. XYZ using the Rasch method. Assessment Value is a measuring tool created to identify and measure the suitability of the candidate's work value. The purpose of making a value assessment is to obtain an assessment design and determine the suitability of the candidate's values with company values. The Rasch method is used to assist research because it facilitates dichotomous data. Dichotomy data consists of two answers, for example, yes or no answers in the assessment. The trial was carried out to obtain an assessment design, which consisted of statistical tests in the form of validity and reliability tests and verification from the user. Test the validity and reliability using computational assistance from the Rasch method on Winstep software. The item assessment validity test is carried out with the help of the item function, while the reliability test uses the summary statistic function in Winstep. User verification is carried out to determine whether the value assessment made is in accordance with the needs and the company's values. The results of the value assessment later can help the company to identify the suitability of the candidate's work culture with the company.